Islamic philosophy on behaviour-based environmental attitude / Mohd Nor Mamat and Siti Fatahiyah Mahamood - Mamat, Mohd Nor; Mahamood, Siti Fatahiyah (Universiti Teknologi MARA Cawangan Selangor, 2017)
This paper concludes philosophical elements regarding conceptual theory, significances of human attitude towards the environment. In a sustainable life, environmental management becomes the most crucial area to be concerned. There are many campaigns, courses and even legal enforcement to ensure the success of educating wise attitude towards environment. This could be more effective and will create eternal effects if the understanding of environmental attitude would be based on religious teachings and philosophy. Not only for Muslims, these theoretical principles were described by the Holy Book, supported with the Prophet‟s tradition which could also be practiced by all mankind. The Great Sustainer is the best provider of the guidelines in interacting with all entities in our environment. In addition, they are closely related to the concept of rewards, directly or delayed. This paper highlighted a conceptual framework to be understood, in order to guide the do‟s and don‟ts, good or bad habits and positive or negative behavior towards environmental entities, including metaphysical entities. The most important point is, this philosophy would be a platform towards designing approaches, strategies or activities towards inculcating good behavior towards environment.